Diseño de arquitectura para la aplicación de Blockchain en un caso de estudio de manufactura aditiva (2020)
Industry 4.0 has been enhanced in recent years due to advances in its related technologies, which benefits the implementation of automated systems in manufacturing. Numerous compilations have been made in the literature on the potential of such technologies, their possible applications and adaptations over more traditional systems. Research is also undertaken on newer technologies such as additive manufacturing (3D printing) and Blockchain, whose combined implementation promises high-level developments. ImpreAndes is a proposal for the application of additive manufacturing on a decentralized network of participants, mounted on the Blockchain technology to take advantage in reliability, transparency and immutability of information. In addition, the design of the architecture of ImpreAndes aims to meet the needs of users of 3D printing within a higher education center, indicating the assets needed for construction and subsequent implementation.--Taken from the Degree Document Format.